10.4197/Mar.32-2.3 Effect of Urbanization Development on Coral Reef at Marsa Alam Coast, Southern Egyptian Red Sea - N. M. Hussein, Hussein (Journal of King Abdulaziz University: Marine Sciences, 2022)
Assessment and distribution of coral reefs at three sites located at the coastof Marsa Alam city southern Egyptian Red Sea were surveyed for the biotic and abiotic components of the sea bottom in order to evaluate the impacts of the urbanization development. The survey was conducted using diving equipment in summer 2020. Line intercepted transect was used to determine corals and other benthic components. The average percentage cover of live corals was 63.27± 7.16. Site 3 has the highest percent cover of live corals (67.6 %) whereas site 1 has the lowest value of live coral reef (55%). Higher degraded reefs above the 2 m and 5 m depth zones characterize coral reefs in the studied sites, dead coral at Study sites coverage was 27.8%, 22.9% and 20.6% at sites 1, 2 and 3, respectively. However, the newly broken colonies were highest at site 1 (2.7%) than at sites 2 (1.4 %) and site 3 (0.9 %). Shannon diversity index H` ranged from 0.65 at site 1 to 0.67 at site 3; The current study revealed that the coral reef was threatened from urbanization development in studied sites, in comparison toother sites that restricted from urban activity. Our conclusion to decision maker is to do the strategic planning and manage to the integrated coastal zone management in future at the Red Sea coast.